2009
DOI: 10.1155/2009/568431
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1,GSTM3andGSTT1Gene Variants and Risk of Benign Prostate Hyperplasia in North India

Abstract: Abstract. Glutathione S-transferases (GSTs) play an important role in detoxification of various toxic compounds like carcinogens in cigarette smoke and tobacco by conjugating to toxic compounds and inactivating their hazardous effect. Variation in Glutathione S-Transferases (GSTs) genes may alter the catalytic efficiency of GST isoenzymes leading to potential increase in cancer susceptibility due to various carcinogens. We therefore, investigated association of GSTM1, GSTM3 and GSTT1 variants with susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Absence of these enzymes due to homozygous deletions is implicated in poor elimination of carcinogenic substances, making individuals with these deletions susceptible to oxidative injury [34] . A study has reported a positive association of GSTM1 or GSTT1 polymorphism with increased risk of BPH [35] . In individuals with BPH and with double deletions GSTM1 -/GSTT1 -, significantly higher MDA levels were observed compared to GSTM1 + / GSTT1 + [34] .…”
Section: Role Of Depletion Of Antioxidant Activitymentioning
confidence: 99%
“…Absence of these enzymes due to homozygous deletions is implicated in poor elimination of carcinogenic substances, making individuals with these deletions susceptible to oxidative injury [34] . A study has reported a positive association of GSTM1 or GSTT1 polymorphism with increased risk of BPH [35] . In individuals with BPH and with double deletions GSTM1 -/GSTT1 -, significantly higher MDA levels were observed compared to GSTM1 + / GSTT1 + [34] .…”
Section: Role Of Depletion Of Antioxidant Activitymentioning
confidence: 99%
“…Human GSTs can be divided into five main classes of enzymes: alpha, mu, pi, theta, and zeta. Of these, GSTP1 (located on 11q13), GSTT1 (on 22q11.23), and GSTM1 (on 1p13.3) exhibit genetic polymorphisms that may lead to altered enzyme activity, which has been associated with many diseases [25][26][27]. GSTP1 exhibits a polymorphism within its coding region (A to G transition at nucleotide +313, thus changing codon 104 from ATC [Ile] to GTC [Val]), which leads to decreased enzyme activity [28].…”
Section: Gst and Risk Of Gerdmentioning
confidence: 99%
“…However, the exact mechanism by which GST polymorphisms might lead to higher cancer risk is not well understood. Studies also report risk of BPH due to GST polymorphism [15]. Hence, the present pilot study was planned to investigate the association of concomitant deletions of GST genes with a marker of oxidative stress in subjects with BPH or prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of these enzymes due to homozygous deletions are implicated in poor elimination of carcinogenic substances including constituents of tobacco which are potential sources of ROS in our body, making individuals with these deletions susceptible to oxidative injury [10]. Studies have reported positive association of GSTM1 or GSTT1 polymorphism with increased risk of BPH and prostate cancer [11][12][13][14][15]. Since these individual deletions are reported to be associated with increased risk, effect of deletion of both these genes could be additive.…”
Section: Introductionmentioning
confidence: 99%